Photochemical [2+2] Cyclization of Helical Phosphinamides in Solution and in the Solid State. Issue 12 (26th September 2017) - Demmer, Charles S.; Aillard, Paul; Febvay, Julie; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract: Phosphole‐based phosphahelicenes which entail unprecedented phosphinamide functions have been prepared. One of these diastereomeric phosphinamides displays an unusual propensity to intermolecular photochemical [2+2] cyclization leading to a bis‐phosphahelicene. The reaction affords the head‐to‐tail heterochiral diastereomer with total regio‐ and diastereoselectivity. The reaction has been observed not only in solution but also in the solid state, as a single‐crystal‐to‐single‐crystal process, under either X‐ray or sunlight irradiation. The solid‐state arrangement of the starting compound strongly prefigures the geometry of the final dimeric species and accounts for the particular ease by which this reaction takes place. The second diastereomer of the phosphinamide does not undergo dimerization under analogous photochemical conditions which can be attributed to an unfavourable arrangement in the solid state. Abstract : Dimers : Supramolecular assembly of a phosphahelicene‐derived phosphinamide in the solid state facilitates its intermolecular [2+2] photocyclization into a bis‐helical cyclobutane. The process takes place with a conversion rate of >90 %, total selectivity toward the heterochiral dimer and total diastereo‐selectivity.